Pregnancy-related sacral stress fractures: A single center experience of 23 cases - Çataltape, Aziz; Baş, Serap (Springer, 2023)
Purpose This study aims to find out the incidence, etiology, and risk factors, define clinical features, show the magnetic resonance imaging (MRI) and laboratory findings, and share the experience of treatment and clinical outcome of pregnancy-related sacral stress fractures (SSFs).Methods In total, 29,291 (15,008 of them vaginal and 14,283 of them cesarean section delivery) women gave birth in our hospital between January 2016 and December 2021. Twenty-three of them (0.078%) who had low back and pelvic pain were diagnosed with SSFs using pelvic MRI. Dual-energy X-ray absorptiometry (DEXA) was used to rule out underlying osteopenia and osteoporosis and determine the type of SSFs.Results The incidence of pregnancy-related SSFs was 0.078% (23/29,291patients). Six patients (26%) experienced pain during the last trimester of pregnancy, remaining seventeen (74%) patients had pain during the postpartum period. 73.91% of the patients were primigravida. Thirteen patients (56.52%) were classified as fatigue SSFs, eight (34.78%) were insufficiency SSFs, and only two (8.7%) were defined as a mixed type of SSFs. MRI imaging showed that nine patients (39.13%) had a left-sided fracture, seven patients (30.43%) had a right-sided fracture, and seven patients (30.43%) had bilateral fractures. Vitamin D deficiency (less than 20 ng/mL) was detected in seven patients (30.44%). One case had hypothyroidism in which thyroid stimulating hormone (TSH) was 5.41 mu IU/mL.Conclusion Pregnancy-related SSFs are uncommon but should be considered by clinicians in the differential diagnosis of low back and pelvic pain during pregnancy and the postpartum period. We determined that first pregnancy is a risk factor for SSFs. The current study also revealed that laboratory investigation of vitamin D deficiency and DEXA investigation, which may lead to osteoporosis or osteopenia, were crucial in the diagnosis. Furthermore, some SSFs should be reclassified as mixed fractures, fatigue, and insufficiency fractures.
Keywords: Dual-Energy X-Ray Absorptiometry; First Pregnancy; Sacral Stress Fractures; Vitamin D Deficiency